The graphic novel - Hoppenstand, Gary (Ipswich, Massachusetts : Salem Press ; Amenia, N.Y. : Grey House Publishing, 2014)
"The Graphic Novel offers an examination and analysis of the contemporary graphic novel as literature. Specific attention will be paid to the use of narrative genre in the graphic novel (e.g. the superhero graphic novel, the crime narrative graphic novel, the horror graphic novel, and the realistic/fantastic graphic novel). Attention will also be paid to the most important and most frequently discussed graphic novels published during the past three decades, including Batman: The Dark Knight Returns by Frank Miller, Watchmen by Alan Moore and Dave Gibbons, The Crow by J. O'Barr, Sin City: The Hard Goodbye by Frank Miller, The Walking Dead: Days Gone Bye by Robert Kirkman and Tony Moore, Road to Perdition by Max Allan Collins and Richard Piers Rayner, A Contract with God and Other Tenement Stories by Will Eisner, Maus by Art Spiegelman. Persepolis: The Story of a Childhood by Marjane Satrapi, and Sandman: Preludes and Nocturnes by Neil Gaiman, Sam Kieth (et al)."--Publisher's website.
Critical contexts. The superhero narrative and the graphic novel / Joseph J. Darowski ; The horror narrative and the graphic novel / Lance Eaton ; The crime narrative and the graphic novel / Rich Shivener ; The reality/fantasy narrative and the graphic novel / Rikk Mulligan -- Critical readings. Wil Eisner's A contract with God / Daniel D. Clark ; Art Spiegelman's Maus : a survivor's tale / Brian Cogan ; Frank Miller's Batman / Jeffrey Johnson ; Alan Moore and Dave Gibbons' Watchmen / Michael G. Robinson ; Alan Moore and David Lloyd's V for Vendetta / Cathy Leogrande ; Neil Gaiman's Sandman / Mary Catherine Harper ; Frank Miller's Sin City / Terrence Wandtke ; Max Allan Collins' Road to Perdition / Jared Griffin ; Marjane Satrapi's Persepolis / Adam Capitanio ; Robert Kirkman and Tony Moore's The walking dead / Michael J. Blouin.
Includes bibliographical references (pages 197-203) and index.
Keywords: Graphic novels -- History and criticism; Comicroman